A taxonomic review of the genus Megalostomis Chevrolat (Coleoptera, Cryptocephalinae, Chrysomelidae) - Agrain, Federico A. (Zootaxa, 2013)
A taxonomic revision of the genus Megalostomis Chevrolat, 1836 (Coleoptera: Chrysomelidae: Cryptocephalinae: Clytrini: Megalostomina) is provided, including new data on geographic ranges. Two new species and 34 new synonymies are proposed within the genus Megalostomis, leaving 42 valid species in the genus. A checklist of the species of Megalostomis is provided, with information on host plants, ant associations, and natural enemies. The study includes a key to all species, diagnoses, descriptions, habitat, photographs, and distribution maps. This comparative study of the external and internal adult morphology includes the male and female genitalia. Nomenclatural acts proposed in this revision are as follow: Change of status: M. dynamica stat. rev. (=M. flavipennis dynamica Monrós, 1952). New synonymy: M. anachoreta Lacordaire, 1848 (=M. gratiosa Lacordaire, 1848, syn. nov., M. amazona Jacoby, 1876, syn. nov., M. generosa Baly, 1877a, syn. nov., M. balyi Monrós, 1951a, syn. nov., M. mariae Monrós 1951a, new status syn., M. hespenheidi Moldenke, 1981, syn. nov.); M. basilaris Jacoby, 1880 (= M. runa Monrós, 1952, syn. nov.); M. cornuta Lacordaire, 1848 (=M. cornuta var. divisa Guérin, 1949, syn. nov.); M. dimidiata dimidiata (Lacordaire, 1848) (= M. tomentosa tomentosa Jacoby, 1880, syn. nov., M. punctatissima (Jacoby, 1888), syn. nov., M. tomentosa orientalis Moldenke, 1970, syn. nov., M. tomentosa sinaloensis Moldenke, 1970, syn. nov., M. tomentosa guatemalensis Achard, 1926 (2nd specimen only), syn. nov., M. dimidiata nayaritensis Moldenke, 1970, syn. nov., M. dimidiata sonorensis Moldenke, 1970, syn. nov.); M. flavocincta Lacordaire, 1848 (=M. flavomaculata Lacordaire, 1848, syn. nov.); M. fulvipes fulvipes Jacoby, 1888 (=M. fulvipes yucatanensis Moldenke, 1970, syn. nov.); M. gazella Lacordaire 1848 (=M. bicingulata, Lacordaire, 1848, syn. nov., M. meretrix Lacordaire, 1848, syn. nov.); M. luctuosa Lacordaire, 1848 (=M. iracunda Lacordaire, 1848, syn. nov.); M. microcephala Lacordaire, 1848 [=M. tosta (Monrós, 1950), syn. nov.]; M. notabilis notabilis Lacordaire, 1848 (=M. notabilis linearis Moldenke, 1970, syn. nov.); M. pyropiga pyropiga Lacordaire, 1848 (=M. pyropiga chiapensis Moldenke, 1970, syn. nov.); M. querula Lacordaire, 1848 (=M. propinqua Lacordaire, 1848, syn. nov., M. univittata pacifica Monrós, 1953a, syn. nov.); M. religiosa Lacordaire, 1848 (=M. distincta Lacordaire, 1848, syn. nov.); M. splendida splendida Lacordaire, 1848 (=M. splendida affinis Jacoby, 1888, syn. nov.; M. splendida regalis Achard, 1926, syn. nov.); M. subfasciata subfasciata (LeConte, 1868) [= M. subfasciata majorubrofasciata Moldenke, 1970, syn. nov.; M. subfasciata murina (Monrós, 1952), syn. nov.]; M. tricincta (Germar, 1824) (=M. bubalus bubalus Lacordaire, 1848 syn. nov., M. bubalus bubaloides Monrós, 1953a, syn. nov.); M. univittata Lacordaire, 1848 (=M. univittata oblita Monrós, 1953a, syn. nov.); M. viridana Lacordaire, 1848 (=M. metallica Jacoby, 1888, syn. nov.). Type designations: lectotypes are designated for the following species: M. anachoreta Lacordaire, 1848; M. chalybeosoma Lacordaire, 1848; M. coerulea Baly, 1877a; M. cornuta Lacordaire, 1848; M. dimidiata Lacordaire, 1848; M. flavipennis Jacoby, 1880; M. flavocincta Lacordaire, 1848; M. gazella Lacordaire, 1848; M. gigas Lacordaire, 1848; M. interruptofasciata Baly, 1877a; M. luctuosa Lacordaire, 1848; M. notabilis Lacordaire, 1848; M. obesa Lacordaire, 1848; M. placida Baly, 1877b; M. pyropiga Lacordaire, 1848; M. religiosa Lacordaire, 1848; M. splendida Lacordaire, 1848; M. subfasciata (LeConte, 1868); M. tricincta (Germar, 1824); M. unicincta Lefèvre, 1884; M. univittata Lacordaire, 1848; M. viridana Lacordaire, 1848; M. microcephala Lacordaire, 1848.